2022
DOI: 10.12659/msm.936535
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19: Another Cause of Dental Anxiety?

Abstract: Background Fear has always been closely linked to dentistry but it could be intensified by the objective risks imposed by the pandemic. The objective of this study was to determine the profile of the frightened dental patient during the COVID-19 pandemic and determine measures taken by dentists to reduce fear and increase security among their patients. Material/Methods An anonymous online survey was conducted between March 15 and April 15, 2021. The respondents were 206… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 30 publications
1
7
0
3
Order By: Relevance
“…Another explanation is that the static management caused by the COVID-19 pandemic intensified the dental anxiety of potential patients. Investigation focusing on the attitude of patients toward dental visits during the COVID-19 pandemic showed that the majority of individuals defined dental offices as high-risk places and hotspots for the transmission of COVID-19 [ 29 ]. Thus, nearly 50% of patients presented fear of dental visits during the pandemic, which was significantly higher than that in the days before the outbreak [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another explanation is that the static management caused by the COVID-19 pandemic intensified the dental anxiety of potential patients. Investigation focusing on the attitude of patients toward dental visits during the COVID-19 pandemic showed that the majority of individuals defined dental offices as high-risk places and hotspots for the transmission of COVID-19 [ 29 ]. Thus, nearly 50% of patients presented fear of dental visits during the pandemic, which was significantly higher than that in the days before the outbreak [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Investigation focusing on the attitude of patients toward dental visits during the COVID-19 pandemic showed that the majority of individuals defined dental offices as high-risk places and hotspots for the transmission of COVID-19 [ 29 ]. Thus, nearly 50% of patients presented fear of dental visits during the pandemic, which was significantly higher than that in the days before the outbreak [ 29 ]. In addition, static management was found to be a risk factor for individuals’ financial crises [ 29 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…dengan sebanyak 2.060 responden yaitu 50% responden merasa takut pergi ke dokter gigi selama pandemi, 20% menganggap klinik gigi sebagai tempat terjadinya penularan SARS-CoV-2, dan 43% mengunjungi dokter gigi hanya dalam keadaan darurat. 23 Hal ini dikarenakan pasien merasa cemas dan takut tertular infeksi di lingkungan dokter gigi, sehingga mengakibatkan adanya peningkatan jumlah kunjungan yang dibatalkan serta penurunan jumlah pemeriksaan pertama dan kunjungan dari pasien baru. 24,25 Selama pandemi Covid-19 agar masyarakat bisa berkonsultasi mengenai kesehatan gigi dan mulut tanpa tatap muka maka digunakanlah metode berupa teledentistry.…”
Section: Hasilunclassified
“…Studies showed the use of protective equipment like hair caps, face shields, and environmental disinfection protocols has significantly improved in dental practice after COVID-19 outbreak. 1 , 2 There have already been a variety of studies exploring the impact of the Covid-19 pandemic on dentistry including the aspect of the dentists and the patients. 3 However, in orthodontic field specifically, there have been few studies on similar topics regarding the influence of the pandemic on the orthodontic patients’ pattern change in decision making and concerns.…”
Section: Introductionmentioning
confidence: 99%